Validation of CFD-DEM simulation of a liquid–solid fluidized bed by dynamic analysis of time series - Picabea, Julia Valentina (2022)
Liquid–solid fluidized beds (LSFB) modeling validation is crucial for establishing design rules and monitoring tools. However, it generally relies on comparing global variables, which overlook dynamic features that influence reaction outputs. This work aims to implement time series analysis tools to compare Radioactive Particle Tracking data with a simulation consisting of Computational Fluid Dynamics coupled with Discrete-Element Method. Experiments have been performed in a pilot-scale LSFB of calcium alginate spheres fluidized with a calcium chloride solution. The Diks’ test indicates that the simulation can capture the LSFB behavior. It also allows diagnosing flow regime transitions from the simulation. Trends of solid dispersion coefficients and mixing times predicted by the simulation are in good agreement with the experiments.